The butterfly - Polacco, Patricia (New York : Philomel Books, 2000)
During the Nazi occupation of France, Monique's mother hides a Jewish family in her basement and tries to help them escape to freedom.
Record updated by Marcive processing 21 June 2024
Keywords: Jews -- France -- Juvenile fiction; World War, 1939-1945 -- France -- Juvenile fiction; France -- History -- German occupation, 1940-1945 -- Juvenile fiction; Fiction